(untitled) (Balkan Journal of Applied Mathematics and Informatics, 2025)
In modern technological and industrial development, the application of electronics in measuring, processing, storing and transferring process data in industrial facilities is increasing. In this processing of process parameters, it is essential that users have timely and accurate information about the measurement data in their industrial complex. Modern electronic systems provide the ability to process and store measurement data on-site and transfer it to the IoT and GSM network. On the other hand, the application of sophisticated electronic systems is noticeable not only in power plants, but also in healthy and quality food industries, such as agriculture. We witness daily tribunes and panel discussions sponsored by companies and even governments for the introduction of the terminology of digital agriculture, i.e. the introduction of smart electronic solutions in agriculture. In addition to the commitment to so-called green energy, i.e. obtaining energy from renewable sources, the development of digitization in agriculture is an area in which an enormous application of smart electronic systems is expected in the future. Guided by these reasons, in this paper an electronic system is designed that provides a solution to a problem in hydro melioration system, i.e. the development, design and practical implementation of the Smart electronic system which enables the measurement of the process parameters of an agro-industrial facility and their transfer to the GSM SIM network. The solution enables the visualization of process parameters locally on LCD displays and remotely on an mobile device in GSM SIM network. A data log file is also provided for store the value on the process parameters ​​on a local computer.